The Role of graRS in Regulating Virulence and Antimicrobial Resistance in Methicillin-Resistant Staphylococcus aureus - Chen, Le; Wang, Zihui; Xu, Tao; Ge, Hongfei; Zhou, Fangyue; Zhu, Xiaoyi; Li, Xianhui; Qu, Di; Zheng, Chunquan; Wu, Yang; Zhao, Keqing (Frontiers in Microbiology, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) is a common cause of both community- and hospital-associated infections. The antibiotic resistance and virulence characteristics of MRSA are largely regulated by two-component signal transduction systems (TCS), including the graRS TCS. To make a relatively comprehensive insight into graRS TCS in MRSA, bioinformatics analysis of dataset GSE26016 (a S. aureus HG001 WT strain vs. the ΔgraRS mutant) from Gene Expression Omnibus (GEO) database was performed, and a total of 563 differentially expressed genes (DEGs) were identified. GO analysis revealed that the DEGs were mainly enriched in the 'de novo' IMP biosynthetic process, lysine biosynthetic process via diaminopimelate, and pathogenesis; and they were mainly enriched in purine metabolism, lysine biosynthesis, and monobactam biosynthesis in KEGG analysis. WGCNA suggested that the turquoise module was related to the blue module, and the genes in these two modules were associated with S. aureus virulence and infection. To investigate the role of graRS in bacterial virulence, a graRS knockout mutant (ΔgraRS) was constructed using MRSA USA500 2395 strain as a parent strain. Compared to the wild-type strain, the USA500ΔgraRS showed reduced staphyloxanthin production, retarded coagulation, weaker hemolysis on blood agar plates, as well as a decreased biofilm formation. These altered phenotypes were restored by complementation of a plasmid-expressed graRS. Meanwhile, expression of the virulence-associated genes (coa, hla, hlb, agrA, mgrA) was down-regulated in the ΔgraRS mutant. Consistently, the A549 epithelial cells invasion of the ΔgraRS mutant was 4-fold lower than that of the USA500 wild-type strain. Moreover, on the Galleria mellonella infection model, the survival rate at day 5 post infection in the USA500ΔgraRS group (55%) was obviously higher than that in the USA500 group (20%), indicating graRS knockout leads to a decreased virulence in vivo. In addition, the deletion of the graRS in the MRSA USA500 strain resulted in its increased susceptibilities to ampicillin, oxacillin, vancomycin, and gentamicin. Our work suggests that the graRS TCS plays an important role in regulating S. aureus virulence in vitro and in vivo, and modulate bacterial resistance to various antibiotics.